A two-step annealing process for enhancing the ferroelectric properties of poly(vinylidene fluoride) (PVDF) devices. Issue 10 (29th January 2015) - Park, Ji Hoon; Kurra, Narendra; AlMadhoun, M. N.; Odeh, Ihab N.; Alshareef, H. N.
Abstract : We report a simple two-step annealing scheme for the fabrication of stable non-volatile memory devices employing poly(vinylidene fluoride) (PVDF) polymer thin-films. Abstract : We report a simple two-step annealing scheme for the fabrication of stable non-volatile memory devices employing poly(vinylidene fluoride) (PVDF) polymer thin-films. The proposed two-step annealing scheme comprises the crystallization of the ferroelectric gamma-phase during the first step and enhancement of the PVDF film dense morphology during the second step. Moreover, when we extended the processing time of the second step, we obtained good hysteresis curves down to 1 Hz, the first such report for ferroelectric PVDF films. The PVDF films also exhibit a coercive field of 113 MV m −1 and a ferroelectric polarization of 5.4 μC cm −2 .